Lotte civili a Milano, tra terrorismo e mafia (1968-1993) - Nando dalla Chiesa (Laboratoire Italien)
The article analyzes how Milanese society has fought two phenomena that attacked it over the 25 years between 1968 and 1993 (the year of the indictment of the socialist leader Bettino Craxi and the mafia massacre in Via Palestro): terrorism –especially left-wing terrorism– and mafia. In other words, it seeks to frame the history of the richest and most cosmopolitan metropolis in Italy from a special point of view. The article does not deal with the economic and trade union struggles, nor with the political struggles of Bettino Craxi, the League or Silvio Berlusconi, but with the people’s struggle against two direct enemies of democracy and legality. It thus offers some critical notes on the history of two different movements. Both were rather linked to civil society than to politics or the world of work. Both played an important role in the defense of the institutions. The antiterrorism movement was less structured and visible, while the antimafia one was more attended and organized. Both were forced to confront diffidence and cultural prejudices; finally, both were animated, especially the latter, by a strong youth and student component. The story and the analysis are born and fed by the direct memory of the author who for different reasons has participated in the two movements intensely: in the second case also playing a leadership role. The genre chosen is therefore that of the “sociological diary”.